2021
DOI: 10.2991/assehr.k.211122.022
|View full text |Cite
|
Sign up to set email alerts
|

How Is the Thinking Process of Students in Solving Math Problems Based on the Adversity Quotient in High School?

Abstract: Mathematics is always related to simple problems to complex problems. The problems given affect the thinking process of students. The problem-solving process also requires hard work to overcome the existing difficulties or what is called the adversity quotient. This study aims to determine the thought processes of climber and quitter in solving math problems. This research is qualitative research, with research subjects consisting of nine students from class eleven in senior high school. Subject selection usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…When understanding the problem, both subjects analyze the information about the problem by identifying the known information and asking questions using their own language mathematically. Riswang et al (2021) explained that in identifying problems and determining goals, AQC subjects use their own words to express aspects of the question that are known and asked. Karimah et al (2018) also concluded that students in the climber category are able to identify existing information and relationships between information relevant to problemsolving.…”
Section: Discussionmentioning
confidence: 99%
“…When understanding the problem, both subjects analyze the information about the problem by identifying the known information and asking questions using their own language mathematically. Riswang et al (2021) explained that in identifying problems and determining goals, AQC subjects use their own words to express aspects of the question that are known and asked. Karimah et al (2018) also concluded that students in the climber category are able to identify existing information and relationships between information relevant to problemsolving.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematics is one of the most important tools for the development of thinking skills, these skills are needed by students to describe ideas in the form of recognizable abilities and intelligence and to solve problems (Bradbury, 2013;Kızıltoprak & Köse, 2017). When students are faced with a problem, it will affect the thinking process in such a way that the student finally knows the answer to the problem (Nurpratiwi & Setianingsih, 2021;Pamungkas et al, 2021). Thinking skills are important for educated people to face a rapidly changing world (Cottrell, 2023;Gough, 1991).…”
Section: A Introductionmentioning
confidence: 99%